Alimentação do lactente com fissura labiopalatina no primeiro ano de vida - Luiz, Aline Godoi [UNESP] (2017)
Objective: To analyze feeding history and maternal experience with breastfeeding infants with cleft lip and palate. Method: descriptive, cross - sectional, double - approach study: quantitative and qualitative, performed at the outpatient clinic of a reference hospital. Data were collected through structured interviews with 150 mothers; 6 mothers participated in the qualitative study. Univariate and multiple logistic regression analyzes were used, adopting as criterion for inclusion in the multiple model p≤0.20. To consider a factor as associated to the outcome, p was considered critical <0.05, in the multiple analysis. These analyzes were performed in the SPSS program. For the qualitative approach the sample was selected for convenience. The statements of the mothers were transcribed in their entirety and analyzed according to the theoretical framework of content analysis according to the steps proposed by Graneheim and Lundman. After analyzing all the qualitative interviews, a framework was constructed with the themes found from the testimonies, being categorized in themes and sub-themes. Results: Less than half of the mothers knew of the prenatal diagnosis and this factor was associated with exclusive breastfeeding in the first week of life, the physician was responsible for the prenatal guidelines. The prevalent type of fissure was unilateral incisive transforamen and on nutritional status, eutrophy prevailed. The strengths, difficulties and challenges faced by the birth of a child with cleft lip and palate were also verified through latent content analysis. Conclusion: the importance of the guidance of health professionals and the time of discovery of the diagnosis of fissure was evidenced, facilitating thus the coping process and breastfeeding. It demonstrates the need for prior training of all the professionals who will work in the pre- and post-natal period.